Climate Smart Agriculture Building Resilience to Climate Change - Lipper, Leslie; McCarthy, Nancy; Zilberman, David; Asfaw, Solomon; Branca, Giacomo (Natural Resource Management and Policy, 2018)
This book is open access under a CC BY-NC-SA 3.0 IGO license.